KARAKTERISTIK OPERATOR PARANORMAL- * QUASI - Gunawan Gunawan; Erni Widiyastuti (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2022)
Given Hilbert space  H  over the fields of  . This study aimed to investigate the paranormal- * quasi operators and their properties in Hilbert space. The study resulted the properties of paranormal- * quasi operators, hyponormal operator, class A operator, Class A- * operator, p- hyponormal operator for p > 0,   - paranormal operators, compact operator, and the relationship between them